Elaboration of Criteria on Leasing Payment Determination in Motor Transport - T. R. Kisel (Наука и техника)
Economically justified composition and size of leasing payments are considered as a central and important part of leasing transactions in motor transport. The purpose of leasing payment is to compensate cost of motor transport facilities, accumulate capital and stimulate business activity. Though from the point of view of transport enterprise management some structural elements of leasing payments do not differ the paper recommends to take into account their specific functions because this point has an important theoretical and practical meaning. High and low rates of leasing payments are also given in the paper.